Educating for diversity, equity, and inclusion: A review of commonly used educational approaches. Issue 1 (9th August 2021) - Corsino, Leonor; Fuller, Anthony T.
Abstract: Diversity, equity, and inclusion (DEI) are fundamentally important concepts for advancing clinical and translational science (CTS) education. CTS education spans a wide range of disciplines from cell biology to clinical and community/population research. This large scope both in terms of intellectual areas and target groups requires an understanding of existing educational approaches for DEI as we translate DEI from mere concepts into equitable actions within CTS education. In this  review, we provide the readers with the most common DEI educational approaches, including cultural humility, bias training, and improving mentoring to diversify the workforce. DEI educational materials can achieve maximal success and long-term impact when implemented as institutional-wide interventions, and the materials are not seen as an isolated or independent curriculum. Approaches, strategies, and programs to achieve this are many. However, many questions remain unanswered about what the best approach, strategies, and programs are to be implemented in institutional-wide education that will be embedded in CTS education.